A porous silicon-carbon composite negative electrode material and preparation method thereof and lithium ion battery
Through the use of porous silicon-carbon composite negative materials in lithium ion batteries, the problem of poor silicon negative cycle performance is solved, and better conductive performance and cycle performance are achieved.
Patent Information
- Application Number
- CN202210976642.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-08-15
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2042-08-15
AI Technical Summary
In the prior art, the silicon negative electrode has poor circulation performance when used in lithium-ion batteries, mainly due to the stress caused by volume expansion and contraction, causing the electrode material to powder and fall off, resulting in rapid attenuation of the battery capacity.
The porous silicon-carbon composite negative material is used. After impregnating the porous silicon in the alkae, the conductive polymer is covered and sintering, forming a porosity silicon-carbon composite material with rich pore structure to relieve volume expansion stress, improve conductive performance and circulation performance.
Improve the conductive performance through the surface -covered carbon material, the rich pore structure relieves the volume expansion stress, avoids the powdery and falling of the electrode material, and significantly improves the cycle performance of lithium ion battery.
Smart Images

Figure CN115241440B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a porous silicon-carbon composite negative electrode material and a preparation method thereof, and a lithium ion battery. Background Art
[0002] Due to the advantages of small size and high energy density, lithium-ion batteries are widely used in various mobile electronic devices and new energy vehicles and other industries.
[0003] Currently, most commercial lithium-ion battery negative electrode materials are graphite; when graphite is used as a negative electrode material, it has the advantage of good cycle stability, but the theoretical capacity of graphite is low, which makes it difficult to meet the requirements of mobile electronic devices and new energy vehicles for power endurance and charging time.
[0004] Silicon anode has the advantages of high theoretical specific capacity (theoretical capacity at room temperature is 3579mAh / g) and low charge and discharge voltage (<0.5V), making it one of the candidates for new lithium-ion battery anode materials. However, silicon anode will undergo severe volume expansion and contraction during the alloying and dealloying process. The stress generated during the volume change will cause the electrode material to pulverize and fall off the current collector, resulting in rapid battery capacity decay and poor cycle performance. Summary of the invention
[0005] The technical problem to be solved by the present invention is: in order to solve the problem of poor cycle performance when silicon negative electrodes are used in lithium ion batteries in the prior art, the present invention provides a method for preparing a porous silicon-carbon composite negative electrode material. The preparation method uses porous silicon as a silicon source, and obtains a porous silicon-carbon composite negative electrode material by impregnating the porous silicon in an alkane, coating the surface of the porous silicon with a conductive polymer, and calcining the porous silicon. The porous silicon-carbon composite negative electrode material has a rich pore structure, can effectively relieve volume expansion stress, ensure sufficient infiltration of the electrolyte, and improve the cycle performance, thereby solving the problem of poor cycle performance when silicon negative electrodes are used in lithium ion batteries in the prior art.
[0006] The technical solution adopted by the present invention to solve its technical problem is:
[0007] A method for preparing a porous silicon-carbon composite negative electrode material comprises the following steps:
[0008] S1: immersing the porous silicon particles in liquid alkane and cooling to 0°C to obtain treated porous silicon;
[0009] S2: adding an acidic solution and a conductive monomer to the treated porous silicon at 0° C. and stirring to obtain a suspension A;
[0010] S3: dissolving the initiator in the acidic solution to obtain solution B;
[0011] S4: adding the solution B dropwise to the suspension A, performing a polymerization reaction at 0° C. to obtain a reaction mixture;
[0012] S5: filtering the reaction mixture to obtain a polymerization product;
[0013] S6: adding the polymer product to n-hexane at 30-50° C., stirring, filtering, washing, and drying to obtain porous silicon coated with a conductive polymer;
[0014] S7: Under the protection of an inert gas, sintering the porous silicon coated with the conductive polymer at 700-1100° C. to obtain a porous silicon-carbon composite negative electrode material.
[0015] Optionally, the liquid alkane is selected from at least one of tetradecane, pentadecane, hexadecane, heptadecane and octadecane.
[0016] Optionally, the conductive monomer is selected from at least one of a thiophene monomer, a pyrrole monomer, and an aniline monomer.
[0017] Optionally, the initiator is selected from at least one of ammonium persulfate, azobisisobutylcyanide, benzoyl peroxide, and anhydrous ferric chloride.
[0018] Optionally, the acidic solutions in step S2 and step S3 are both hydrochloric acid solutions or chloroform solutions.
[0019] Optionally, the mass ratio of the porous silicon particles to the conductive monomer is 1:(1-5).
[0020] Optionally, the molar ratio of the initiator to the conductive monomer is 1:1.
[0021] Optionally, sintering the conductive polymer-coated porous silicon at 700-1100° C. comprises: heating to 700-1100° C. at a heating rate of 5-10° C. / min, and sintering for 1 to 3 hours.
[0022] Another object of the present invention is to provide a porous silicon-carbon composite negative electrode material, which is prepared by the preparation method as described above.
[0023] Another object of the present invention is to provide a lithium-ion battery comprising the porous silicon-carbon composite negative electrode material as described above.
[0024] The beneficial effects of the present invention are:
[0025] The preparation method of the porous silicon-carbon composite negative electrode material provided by the present invention comprises the following steps: before the polymerization reaction, the pores of the porous silicon are first occupied by alkanes through impregnation, so that the obtained porous silicon-carbon composite negative electrode material retains the porous structure of the porous silicon, and only the carbon material is coated on the surface of the porous silicon. Therefore, when the porous silicon-carbon composite negative electrode material is used in a lithium ion battery, the conductive performance can be improved by the carbon material coated on the surface, and the volume expansion stress can be effectively relieved by the rich pore structure, so as to avoid the pulverization of the electrode material and the shedding of the current collector, thereby avoiding the rapid attenuation of the battery capacity and improving the cycle performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] The present invention is further described below in conjunction with the accompanying drawings and embodiments.
[0027] Figure 1 is a SEM photograph of the porous silicon-carbon composite negative electrode material prepared in Example 1 of the present invention;
[0028] Figure 2 is the rate performance curve of the porous silicon-carbon composite negative electrode material prepared in Example 1 of the present invention;
[0029] Figure 3 This is the cycle performance curve of the porous silicon-carbon composite negative electrode material prepared in Example 1 of the present invention at a current density of 1 A / g. DETAILED DESCRIPTION
[0030] The present invention is now further described in detail. The embodiments described below are exemplary and intended to be used to explain the present invention, but cannot be understood as limiting the present invention. All other embodiments obtained by ordinary technicians in this field without creative work based on the embodiments of the present invention belong to the scope of protection of the present invention.
[0031] In order to solve the problem of poor cycle performance of silicon negative electrode in the prior art when used in lithium ion batteries, the present invention provides a method for preparing a porous silicon-carbon composite negative electrode material, which comprises the following steps:
[0032] S1: immersing the porous silicon particles in liquid alkane and cooling to 0°C to obtain treated porous silicon;
[0033] S2: adding an acidic solution and a conductive monomer to the treated porous silicon at 0°C, stirring, and obtaining a suspension A;
[0034] S3: dissolving the initiator in the acidic solution to obtain solution B;
[0035] S4: adding solution B dropwise to suspension A, performing polymerization reaction at 0°C to obtain a reaction mixture;
[0036] S5: filtering the reaction mixture to obtain a polymerization product;
[0037] S6: adding the polymerized product to n-hexane at 30-50° C., stirring, filtering, washing, and drying to obtain porous silicon coated with a conductive polymer;
[0038] S7: Under the protection of an inert gas, the porous silicon coated with the conductive polymer is sintered at 700-1100° C. to obtain a porous silicon-carbon composite negative electrode material.
[0039] The present invention uses porous silicon as a silicon source, firstly immerses porous silicon particles in liquid alkane so that the pores of the porous silicon particles are filled with alkane, then cools to 0°C, the liquid alkane becomes solid, and porous silicon with alkane occupying the pores is obtained, i.e., the treated porous silicon; an acid solution and a conductive monomer are added to the treated porous silicon at 0°C, stirred, and a suspension A is obtained; an initiator is dissolved in the acid solution to obtain a solution B; the solution B is slowly dripped into the suspension A, preferably the dripping time is 10 minutes, and after the dripping is completed, a polymerization reaction is carried out at 0°C, and the conductive monomer is in-situ polymerized on the surface of the treated porous silicon to obtain a polymerization product, which includes porous silicon with alkane occupying the pores, and a conductive polymer coated on the surface of the porous silicon with alkane occupying the pores; after the polymerization is completed, Filter and wash with distilled water to remove the unreacted initiator, etc., then add the obtained polymerization product into 30-50°C n-hexane and stir for 10 minutes, then filter and wash with n-hexane to remove the alkane in the porous silicon pores, and place the polymerization product in a 60°C forced air drying oven for 24 hours to obtain porous silicon coated with a conductive polymer, wherein the porous silicon coated with a conductive polymer includes porous silicon with a porous structure, no conductive polymer in the porous silicon, and conductive polymer coated on the surface of the porous silicon with a porous structure; further sinter the porous silicon coated with a conductive polymer to obtain a porous silicon-carbon composite negative electrode material, wherein the porous silicon-carbon composite negative electrode material includes porous silicon with a porous structure, no carbon material in the porous silicon, and carbon material coated on the surface of the porous silicon with a porous structure.
[0040] The porous silicon in the present invention can be prepared by existing electrochemical methods, photochemical methods, etching methods, hydrothermal corrosion methods, etc. The present invention does not limit the specific preparation process of porous silicon. In order to ensure the electrochemical performance of the porous silicon-carbon composite negative electrode material, the present invention preferably uses a pore volume of 0.047 cm 3 / g of porous silicon is the silicon source.
[0041] The preparation method of the porous silicon-carbon composite negative electrode material provided by the present invention comprises the following steps: before the polymerization reaction, the pores of the porous silicon are firstly occupied by alkanes through impregnation, so that the obtained porous silicon-carbon composite negative electrode material retains the porous structure of the porous silicon, and the carbon material is only coated on the surface of the porous silicon, while no carbon material exists inside the pores. Therefore, when the porous silicon-carbon composite negative electrode material is used in a lithium ion battery, on the one hand, the interior has space required for the volume expansion of silicon during charging, and on the other hand, the carbon material layer coated on the surface of the porous silicon can effectively inhibit the expansion of silicon out of the particles, thereby ensuring the integrity of the composite negative electrode material particles; and, the conductive performance can be improved by the carbon material coated on the surface, and the volume expansion stress can be effectively relieved by the rich pore structure, thereby avoiding the pulverization of the electrode material and the shedding of the current collector, and ensuring the full infiltration of the electrolyte, thereby avoiding the rapid attenuation of the battery capacity and improving the cycle performance.
[0042] In order to ensure the porous effect of the prepared porous silicon-carbon composite negative electrode material, the liquid alkane of the present invention is preferably selected from at least one of tetradecane, pentadecane, hexadecane, heptadecane and octadecane, and the melting points of the above alkanes are all within the range of 5-30°C and are liquid at room temperature, so as to ensure that in the impregnation step, the alkanes can be fully filled in the pores of the porous silicon, and when the temperature drops to 0°C, the above alkanes are all converted into solid state, and further ensure that the subsequent polymerization reaction is carried out at 0°C, so that the pores of the porous silicon are always occupied by solid alkanes during the polymerization reaction, so as to ensure that the conductive polymer generated by the polymerization reaction is only coated on the surface of the porous silicon, and cannot enter the pores of the porous silicon.
[0043] Furthermore, the present invention preferably impregnates the porous silicon particles with liquid alkane in equal volumes at 30-60° C. to ensure that the alkane is in liquid state during the impregnation process, thereby ensuring sufficient impregnation.
[0044] In order to prevent the pore structure in the prepared porous silicon-carbon composite negative electrode material from being occupied by carbon materials, the present invention adopts a low-temperature liquid phase in-situ polymerization method to coat the surface of porous silicon particles, with the purpose of making the coating temperature lower than the melting point of the alkane inside the porous silicon, so that the pore structure inside the porous silicon can be coated on the surface of the porous silicon when it is occupied by the alkane, so that the coating layer will not occupy the pores inside the porous silicon; since polythiophene, polypyrrole and polyaniline can all be polymerized and coated at 0°C, the present invention preferably selects at least one of the conductive monomers selected from thiophene monomers, pyrrole monomers and aniline monomers; and, after sintering, the above conductive monomers can also introduce heteroatoms into the carbon material, thereby further improving the capacitance performance of the composite negative electrode material; further, the present invention preferably selects the conductive monomer as aniline monomer.
[0045] To ensure the smooth progress of the polymerization reaction, the initiator is preferably selected from at least one of ammonium persulfate, azobisisobutylcyanide, benzoyl peroxide, and anhydrous ferric chloride, and the initiator is further preferably ammonium persulfate.
[0046] In the present invention, the acidic solutions in step S2 and step S3 are preferably hydrochloric acid solutions or chloroform solutions, and further preferably the acidic solutions are 1 mol / L hydrochloric acid solutions.
[0047] In order to take into account both the cycle performance and the conductive performance of the porous silicon-carbon composite negative electrode material, the present invention preferably has a mass ratio of porous silicon particles to conductive monomers of 1:(1-5).
[0048] To ensure that the polymerization reaction proceeds fully, the preferred molar ratio of the initiator to the conductive monomer is 1:1.
[0049] To ensure the comprehensive performance of the porous silicon-carbon composite negative electrode material, the present invention preferably sintered the porous silicon coated with the conductive polymer at 700-1100°C, including: heating to 700-1100°C at a heating rate of 5-10°C / min, and sintering for 1-3h.
[0050] Another object of the present invention is to provide a porous silicon-carbon composite negative electrode material, wherein the porous silicon-carbon composite negative electrode material is prepared by the preparation method as described above.
[0051] The porous silicon-carbon composite negative electrode material provided by the present invention, when used in lithium-ion batteries, can improve the conductivity through the carbon material coated on the surface, and effectively relieve the volume expansion stress through the rich pore structure, avoid the pulverization of the electrode material and the shedding of the current collector, and ensure the full infiltration of the electrolyte, thereby avoiding the rapid attenuation of the battery capacity and improving the cycle performance.
[0052] Another object of the present invention is to provide a lithium ion battery, which comprises the porous silicon-carbon composite negative electrode material as described above.
[0053] The lithium ion battery provided by the present invention adopts the porous silicon-carbon composite negative electrode material as described above and has excellent cycle performance.
[0054] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, specific embodiments of the present invention are described in detail below with reference to the accompanying drawings.
[0055] Example 1
[0056] S1: The pore volume is 0.047cm 3 / g porous silicon particles were impregnated with octadecane in equal volumes at 45°C, and then the temperature was lowered to 0°C to obtain treated porous silicon;
[0057] S2: Control the temperature to 0°C, add 80 mL of 1 mol / L hydrochloric acid solution to the round-bottom flask containing the treated porous silicon, and add aniline monomer at a mass ratio of porous silicon to aniline of 1:2, and stir for 30 minutes to obtain suspension A;
[0058] S3: dissolving (NH4)2S2O8 in 20 mL of 1 mol / L hydrochloric acid solution at a molar ratio of aniline to (NH4)2S2O8 of 1:1 to obtain solution B;
[0059] S4: slowly dripping solution B into suspension A for 10 min, polymerizing for 24 h after the dripping is completed, and controlling the reaction temperature to 0°C during the polymerization process to obtain a reaction mixture;
[0060] S5: After the polymerization is completed, the reaction mixture is filtered, and the filtrate is washed with distilled water to remove the unreacted ammonium persulfate to obtain a polymerization product;
[0061] S6: adding the obtained polymer product to 40° C. n-hexane and stirring for 10 min, then filtering and washing with n-hexane to remove the alkane in the porous silicon pores, and placing the polymer product in a 60° C. forced air drying oven to dry for 24 h to obtain porous silicon coated with a conductive polymer;
[0062] S7: Place the porous silicon coated with the conductive polymer into a tubular furnace, and under nitrogen protection, heat it to 900°C at a heating rate of 5°C / min and sinter it for 2h to obtain a porous silicon-carbon composite negative electrode material.
[0063] The porous silicon-carbon composite negative electrode material prepared in this example was tested. Figure 1 As shown, the surface of porous silicon is coated with carbon material.
[0064] The porous silicon-carbon composite negative electrode material was used as a negative electrode material for a lithium-ion battery for performance testing; after testing, see Figure 2 , Figure 3 As shown, the porous silicon-carbon composite negative electrode material exhibits an initial coulombic efficiency of 78% at a current density of 0.1 A / g, a first discharge specific capacity of 2714 mAh / g, a specific capacity of 786 mAh / g at a current density of 3 A / g, and a reversible capacity of 770 mAh / g after 100 cycles at a current density of 1 A / g, showing excellent cycle performance.
[0065] Example 2
[0066] S1: The pore volume is 0.047cm 3 / g porous silicon particles were impregnated with tetradecane in equal volumes at 30°C, and then the temperature was lowered to 0°C to obtain treated porous silicon;
[0067] S2: Control the temperature to 0°C, add 80 mL of 1 mol / L hydrochloric acid solution to the round-bottom flask containing the treated porous silicon, and add aniline monomer at a mass ratio of porous silicon to aniline of 1:1, and stir for 30 minutes to obtain suspension A;
[0068] S3: dissolving (NH4)2S2O8 in 20 mL of 1 mol / L hydrochloric acid solution at a molar ratio of aniline to (NH4)2S2O8 of 1:1 to obtain solution B;
[0069] S4: slowly dripping solution B into suspension A for 10 min, polymerizing for 24 h after the dripping is completed, and controlling the reaction temperature to 0°C during the polymerization process to obtain a reaction mixture;
[0070] S5: After the polymerization is completed, the reaction mixture is filtered, and the filtrate is washed with distilled water to remove the unreacted ammonium persulfate to obtain a polymerization product;
[0071] S6: adding the obtained polymer product to 30° C. n-hexane and stirring for 10 min, then filtering and washing with n-hexane to remove the alkane in the porous silicon pores, and placing the polymer product in a 60° C. forced air drying oven to dry for 24 h to obtain porous silicon coated with a conductive polymer;
[0072] S7: Place the porous silicon coated with the conductive polymer into a tubular furnace, and under nitrogen protection, heat it to 700°C at a heating rate of 7°C / min and sinter it for 2h to obtain a porous silicon-carbon composite negative electrode material.
[0073] The porous silicon-carbon composite negative electrode material was used as a negative electrode material for a lithium-ion battery for performance testing; after testing, the porous silicon-carbon composite negative electrode material showed an initial coulombic efficiency of 72% at a current density of 0.1A / g, a first discharge specific capacity of 3035mAh / g, a specific capacity of 510mAh / g at a current density of 3A / g, and a reversible capacity of 505mAh / g after 100 cycles at a current density of 1A / g, showing excellent cycle performance.
[0074] Example 3
[0075] S1: The pore volume is 0.047cm 3 / g porous silicon particles were impregnated with hexadecane in equal volumes at 60°C, and then the temperature was lowered to 0°C to obtain treated porous silicon;
[0076] S2: Control the temperature to 0°C, add 80 mL of 1 mol / L hydrochloric acid solution to the round-bottom flask containing the treated porous silicon, and add aniline monomer at a mass ratio of porous silicon to aniline of 1:5, and stir for 30 minutes to obtain suspension A;
[0077] S3: dissolving (NH4)2S2O8 in 20 mL of 1 mol / L hydrochloric acid solution at a molar ratio of aniline to (NH4)2S2O8 of 1:1 to obtain solution B;
[0078] S4: slowly dripping solution B into suspension A for 10 min, polymerizing for 24 h after the dripping is completed, and controlling the reaction temperature to 0°C during the polymerization process to obtain a reaction mixture;
[0079] S5: After the polymerization is completed, the reaction mixture is filtered, and the filtrate is washed with distilled water to remove the unreacted ammonium persulfate to obtain a polymerization product;
[0080] S6: adding the obtained polymer product to 50° C. n-hexane and stirring for 10 min, then filtering and washing with n-hexane to remove the alkane in the porous silicon pores, and placing the polymer product in a 60° C. forced air drying oven to dry for 24 h to obtain porous silicon coated with a conductive polymer;
[0081] S7: Place the porous silicon coated with the conductive polymer into a tubular furnace, and under nitrogen protection, heat it to 1100°C at a heating rate of 10°C / min and sinter it for 2h to obtain a porous silicon-carbon composite negative electrode material.
[0082] The porous silicon-carbon composite negative electrode material was used as a negative electrode material for a lithium-ion battery for performance testing; after testing, the porous silicon-carbon composite negative electrode material showed an initial coulombic efficiency of 82% at a current density of 0.1A / g, a first discharge specific capacity of 1836mAh / g, a specific capacity of 630mAh / g at a current density of 3A / g, and a reversible capacity of 646mAh / g after 100 cycles at a current density of 1A / g, showing excellent cycle performance.
[0083] Example 4
[0084] S1: The pore volume is 0.047cm 3 / g porous silicon particles were impregnated with octadecane in equal volumes at 45°C, and then the temperature was lowered to 0°C to obtain treated porous silicon;
[0085] S2: Control the temperature to 0°C, add 50 mL of 1 mol / L chloroform solution to the round-bottom flask containing the treated porous silicon, and add thiophene monomer at a mass ratio of porous silicon to thiophene of 1:2, introduce argon gas and continue stirring for 30 minutes to obtain suspension A;
[0086] S3: dissolving anhydrous ferric chloride in 50 mL of 1 mol / L chloroform solution at a molar ratio of thiophene to anhydrous ferric chloride of 1:4, introducing argon gas and stirring for 30 min to obtain solution B;
[0087] S4: slowly dripping solution B into suspension A for 10 min. After the dripping is completed, argon gas is introduced and the polymerization is continuously stirred for 24 h. During the polymerization, the reaction temperature is controlled at 0°C to obtain a reaction mixture.
[0088] S5: After the polymerization is completed, the reaction mixture is filtered, and the filtrate is washed with distilled water to remove the unreacted ammonium persulfate to obtain a polymerization product;
[0089] S6: adding the obtained polymer product to 40° C. n-hexane and stirring for 10 min, then filtering and washing with n-hexane to remove the alkane in the porous silicon pores, and placing the polymer product in a 60° C. forced air drying oven to dry for 24 h to obtain porous silicon coated with a conductive polymer;
[0090] S7: Place the porous silicon coated with the conductive polymer into a tubular furnace, and under nitrogen protection, heat it to 900°C at a heating rate of 5°C / min and sinter it for 2h to obtain a porous silicon-carbon composite negative electrode material.
[0091] The porous silicon-carbon composite negative electrode material was used as a negative electrode material for a lithium-ion battery for performance testing; after testing, the porous silicon-carbon composite negative electrode material exhibited an initial coulombic efficiency of 70% at a current density of 0.1A / g, a first discharge specific capacity of 2598mAh / g, a specific capacity of 731mAh / g at a current density of 3A / g, and a reversible capacity of 682mAh / g after 100 cycles at a current density of 1A / g, showing excellent cycle performance.
[0092] Example 5
[0093] S1: The pore volume is 0.047cm 3 / g porous silicon particles were impregnated with octadecane in equal volumes at 45°C, and then the temperature was lowered to 0°C to obtain treated porous silicon;
[0094] S2: Control the temperature to 0°C, add 80 mL of 1 mol / L hydrochloric acid solution to the round-bottom flask containing the treated porous silicon, and add pyrrole monomer at a mass ratio of porous silicon to pyrrole of 1:2, and stir for 30 minutes to obtain suspension A;
[0095] S3: dissolving (NH4)2S2O8 in 20 mL of 1 mol / L hydrochloric acid solution according to a pyrrole: (NH4)2S2O8 molar ratio of 1:1 to obtain solution B;
[0096] S4: slowly dripping solution B into suspension A for 10 min, polymerizing for 24 h after the dripping is completed, and controlling the reaction temperature to 0°C during the polymerization process to obtain a reaction mixture;
[0097] S5: After the polymerization is completed, the reaction mixture is filtered, and the filtrate is washed with distilled water to remove the unreacted ammonium persulfate to obtain a polymerization product;
[0098] S6: adding the obtained polymer product to 40° C. n-hexane and stirring for 10 min, then filtering and washing with n-hexane to remove the alkane in the porous silicon pores, and placing the polymer product in a 60° C. forced air drying oven to dry for 24 h to obtain porous silicon coated with a conductive polymer;
[0099] S7: Place the porous silicon coated with the conductive polymer into a tubular furnace, and under nitrogen protection, heat it to 900°C at a heating rate of 5°C / min and sinter it for 2h to obtain a porous silicon-carbon composite negative electrode material.
[0100] The porous silicon-carbon composite negative electrode material was used as a negative electrode material for a lithium-ion battery for performance testing; after testing, the porous silicon-carbon composite negative electrode material showed an initial coulombic efficiency of 76% at a current density of 0.1A / g, a first discharge specific capacity of 2826mAh / g, a specific capacity of 728mAh / g at a current density of 3A / g, and a reversible capacity of 702mAh / g after 100 cycles at a current density of 1A / g, showing excellent cycle performance.
[0101] Comparative Example 1
[0102] S1: The temperature is controlled at 0°C and a pore volume of 0.047 cm 3 / g porous silicon particles were added into a round-bottom flask with 80mL of 1mol / L hydrochloric acid solution, and aniline monomer was added at a mass ratio of porous silicon to aniline of 1:2, and after stirring for 30min, a suspension A was obtained;
[0103] S2: dissolve (NH4)2S2O8 in 20 mL of 1 mol / L hydrochloric acid solution according to the molar ratio of aniline to (NH4)2S2O8 of 1:1 to obtain solution B;
[0104] S3: Slowly drip solution B into suspension A for 10 min. After the dripping is completed, the suspension is polymerized for 24 h. During the polymerization, the reaction temperature is controlled at 0 °C to obtain a reaction mixture.
[0105] S4: After the polymerization is completed, the reaction mixture is filtered, and the filtrate is washed with distilled water to remove the unreacted ammonium persulfate to obtain a polymerization product;
[0106] S5: adding the obtained polymer product to n-hexane at 40° C. and stirring for 10 min, then filtering and washing with n-hexane, and drying the polymer product in a 60° C. forced air drying oven for 24 h to obtain porous silicon coated with a conductive polymer;
[0107] S6: Place the porous silicon coated with the conductive polymer into a tubular furnace, and under nitrogen protection, heat it to 900°C at a heating rate of 5°C / min and sinter it for 2h to obtain a composite negative electrode material.
[0108] The difference between this comparative example and Example 1 is that the porous silicon particles are not treated with alkanes; the composite negative electrode material is used as the negative electrode material of a lithium ion battery for performance testing; after testing, the composite negative electrode material exhibits an initial coulomb efficiency of 75% at a current density of 0.1A / g, a first discharge specific capacity of 2205mAh / g, a specific capacity of 606mAh / g at a current density of 3A / g, and a reversible capacity of 412mAh / g after 100 cycles at a current density of 1A / g. Compared with Example 1, the cycle performance is significantly deteriorated.
[0109] Comparative Example 2
[0110] S1: Control the temperature to 0°C, add 80mL of 1mol / L hydrochloric acid solution to a round-bottom flask containing silicon particles (non-porous silicon), and add aniline monomer at a mass ratio of silicon particles to aniline of 1:2, and stir for 30 minutes to obtain suspension A;
[0111] S2: dissolve (NH4)2S2O8 in 20 mL of 1 mol / L hydrochloric acid solution according to the molar ratio of aniline to (NH4)2S2O8 of 1:1 to obtain solution B;
[0112] S3: Slowly drip solution B into suspension A for 10 min. After the dripping is completed, the suspension is polymerized for 24 h. During the polymerization, the reaction temperature is controlled at 0 °C to obtain a reaction mixture.
[0113] S4: After the polymerization is completed, the reaction mixture is filtered, and the filtrate is washed with distilled water to remove the unreacted ammonium persulfate to obtain a polymerization product;
[0114] S5: adding the obtained polymer product to 40° C. n-hexane and stirring for 10 min, then filtering and washing with n-hexane, and placing the polymer product in a 60° C. forced air drying oven and drying for 24 h to obtain silicon particles coated with a conductive polymer;
[0115] S6: Place the silicon particles coated with the conductive polymer into a tubular furnace, and under nitrogen protection, heat the temperature to 900°C at a heating rate of 5°C / min and sinter for 2 hours to obtain a composite negative electrode material.
[0116] The difference between this comparative example and Example 1 is that non-porous silicon particles are used to replace porous silicon particles; the composite negative electrode material is used as the negative electrode material of a lithium ion battery for performance testing; after testing, the composite negative electrode material exhibits an initial coulomb efficiency of 71% at a current density of 0.1A / g, a first discharge specific capacity of 2225mAh / g, a specific capacity of 501mAh / g at a current density of 3A / g, and a reversible capacity of 484mAh / g after 100 cycles at a current density of 1A / g. Compared with Example 1, the cycle performance is significantly deteriorated.
[0117] Based on the above ideal embodiments of the present invention, the relevant staff can make various changes and modifications without departing from the technical concept of the present invention through the above description. The technical scope of the present invention is not limited to the contents of the specification, and its technical scope must be determined according to the scope of the claims.
Claims
1. A method for preparing a porous silicon-carbon composite negative electrode material, characterized in that: The method comprises the following steps: S1: immersing porous silicon particles in liquid alkane and cooling the temperature to 0° C. to obtain treated porous silicon; S2: adding an acidic solution and a conductive monomer to the treated porous silicon at 0° C. and stirring to obtain a suspension A; S3: dissolving the initiator in the acidic solution to obtain solution B; S4: adding the solution B dropwise to the suspension A, performing a polymerization reaction at 0° C. to obtain a reaction mixture; S5: filtering the reaction mixture to obtain a polymerization product; S6: adding the polymer product to n-hexane at 30-50° C., stirring, filtering, washing, and drying to obtain porous silicon coated with a conductive polymer; S7: Under the protection of an inert gas, sintering the porous silicon coated with the conductive polymer at 700-1100° C. to obtain a porous silicon-carbon composite negative electrode material; The liquid alkane is selected from at least one of tetradecane, pentadecane, hexadecane, heptadecane and octadecane.
2. The method for preparing the porous silicon-carbon composite negative electrode material according to claim 1, characterized in that: The conductive monomer is selected from at least one of a thiophene monomer, a pyrrole monomer, and an aniline monomer.
3. The method for preparing the porous silicon-carbon composite negative electrode material according to claim 1, characterized in that: The initiator is selected from at least one of ammonium persulfate, azobisisobutyl cyanide, benzoyl peroxide, and anhydrous ferric chloride.
4. The method for preparing the porous silicon-carbon composite negative electrode material according to claim 1, characterized in that: The acidic solutions in step S2 and step S3 are both hydrochloric acid solutions or chloroform solutions.
5. The method for preparing the porous silicon-carbon composite negative electrode material according to any one of claims 1 to 4, characterized in that: The mass ratio of the porous silicon particles to the conductive monomer is 1:(1-5).
6. The method for preparing the porous silicon-carbon composite negative electrode material according to any one of claims 1 to 4, characterized in that: The molar ratio of the initiator to the conductive monomer is 1:
1.
7. The method for preparing the porous silicon-carbon composite negative electrode material according to any one of claims 1 to 4, characterized in that: Sintering the conductive polymer-coated porous silicon at 700-1100° C. includes: heating to 700-1100° C. at a heating rate of 5-10° C. / min, and sintering for 1-3 hours.
8. A porous silicon-carbon composite negative electrode material, characterized in that: The preparation is carried out by the preparation method according to any one of claims 1 to 7.
9. A lithium ion battery, characterized in that: It comprises the porous silicon-carbon composite negative electrode material as claimed in claim 8.
Citation Information
Patent Citations
Capacity-controllable type silicon-based lithium ion battery negative electrode material and preparation method therefor
CN107611417A
Preparation of porous silicon hollow sphere coated with high-molecular conductive polymer and product and application thereof
CN109638256A